Safety and tolerability of pioglitazone - Belcher, G; Matthews, DR (2000)
Pioglitazone HCl, a new thiazolidinedione (TZD), has been developed for the treatment of type 2 diabetes. The drug was tested in several trials that included over 5,000 subjects. Of these, over 3,500 subjects received active treatment. At doses between 15-45 mg pioglitazone was well tolerated with dropouts due to adverse events being similar in pioglitazone and placebo groups. The main side effect of treatment was mild to moderate peripheral oedema. Oedema was not associated with signs or symptoms of congestive cardiac failure, and there was no excess of adverse events in the cardiovascular system in the pioglitazone-treated patients. Weight increases were seen during treatment with pioglitazone, with most weight gain in the early period of the treatment, which then stabilised. It has been shown to be due to increases in subcutaneous fat. Despite weight gain, the favourable effects of pioglitazone on glycaemic control and lipids were maintained. In laboratory tests, small decreases in haemoglobin and haematocrit were seen due to haemodilution. However, anaemia was not reported more often with pioglitazone than with placebo and no patients were discontinued due to anaemia associated with pioglitazone. A thorough analysis of results of liver tests revealed no evidence of hepatotoxicity with pioglitazone. The safety profile of pioglitazone demonstrated by clinical trials is supported further by safety data from the market in USA and Japan, where the drug has been widely prescribed for over a year. A safety and tolerability profile, similar to that seen in clinical trials, has been reported. © 2000 Johann Ambrosius Barth.